Discipline Of Staff In The University Of Malaya: The Nemo Judex Rule And The Universities And The Universities College Act 1971 - Majid, Abdul (Journal of Malaysian and Comparative Law, 2019)
Discipline Of Staff In The University Of Malaya: The Nemo Judex Rule And The Universities And The Universities College Act 1971